The Dynamics of the Implementation of the Digital Economy in MSMEs in Buleleng Bali: between Growth Opportunities and Adaptation Challenges - Moh Fakhri Siddiqi; Yesi Sifaiyah (Journal of Economics and Social Sciences (JESS), 2026)
The development of the digital economy has created various new opportunities for Micro, Small, and Medium Enterprises (MSMEs) in improving business performance and competitiveness. However, not all MSMEs are able to adapt optimally to the digital transformation that occurs. This study aims to analyze the dynamics of the implementation of the digital economy in MSMEs in Buleleng Regency, Bali, focusing on growth opportunities and adaptation challenges. The research uses a qualitative approach with phenomenological methods. Data collection was carried out through interviews, observations, and documentation of MSME actors in the trade, culinary, and handicraft sectors. Data analysis uses the Miles, Huberman, and Saldaña model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of the digital economy in MSMEs in Buleleng Regency is still relatively simple and dominated by the use of social media and marketplaces. Digital technology provides opportunities in the form of expanding market reach, increasing sales, ease of customer service, and business efficiency. However, MSME actors still face various challenges in the form of low digital literacy, limited technological capabilities, concerns about online transaction risks, and lack of digital training and assistance. Therefore, synergy is needed between the government and MSME actors to improve digital capabilities to support sustainable business growth.